CURRENCY AND ITS ROLE IN MODERN ECONOMIES - Bolbekova Ug'iloy Jaloliddinovna; Urunova Ruxshona Faxriddin qizi (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract This article examines the economic essence, historical evolution, major functions, and contemporary significance of currency in modern economies. The study explains the transformation of currency from barter and commodity-based exchange to metallic money, paper banknotes, fiat currency, and digital monetary forms. Particular attention is given to the role of currency in market exchange, price formation, savings accumulation, deferred payments, and macroeconomic stability. The article also analyzes the relationship between currency, inflation, exchange rates, and technological innovation in the financial sphere. The findings demonstrate that currency is not merely a technical means of payment, but a fundamental institutional mechanism that supports economic coordination, financial intermediation, and national development. In the context of globalization and digitalization, the future of currency depends on the effective interaction of innovation, public trust, monetary regulation, and financial security.